2021
DOI: 10.22141/2306-2436.8.2.2019.172620
|View full text |Cite
|
Sign up to set email alerts
|

Трофологический Статус Пациентов С Остеоартрозом И Экскреторной Недостаточностью Поджелудочной Железы

Abstract: The trophological status of patients with osteoarthrosis and excretory insufficiency of pancreas Abstract. Background. Studies found a high incidence of the gastrointestinal tract (GI) diseases in patients with OA, especially those that are accompanied by a violation of the excretory insufficiency of pancreas (EIP), which also contributes to the activation of proteolysis. The EIP in patients with OA is formed at the comorbid pathologies: chronic pancreatitis (CP) with EIP and incretory insufficiency in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…Trophological insufficiency is polynutrient in its composition, i. e. lacking macro components (proteins, fats, carbohydrates) and micro components (vitamins and some chemical elements) in different ratios [1]. Trophological insufficiency occurs because of both exogenous agents (inadequate intake of nutrients from food, caused by a sparing diet a patient has to follow due to pain syndrome, as well as irrational diet due to alcohol abuse, socio-economic reasons and low medical awareness) and endogenous agents (malutilization of nutrients in a patient's body) [3,4].…”
Section: оригінальні дослідженняmentioning
confidence: 99%
“…Trophological insufficiency is polynutrient in its composition, i. e. lacking macro components (proteins, fats, carbohydrates) and micro components (vitamins and some chemical elements) in different ratios [1]. Trophological insufficiency occurs because of both exogenous agents (inadequate intake of nutrients from food, caused by a sparing diet a patient has to follow due to pain syndrome, as well as irrational diet due to alcohol abuse, socio-economic reasons and low medical awareness) and endogenous agents (malutilization of nutrients in a patient's body) [3,4].…”
Section: оригінальні дослідженняmentioning
confidence: 99%
“…Recent studies have shown a significant effect on the condition of the pancreas in patients with primary osteoarthritis (OA) [1][2][3]. It is known that the basis of endocrine disorders in chronic pancreatitis (CP) is the morphological features of the location of the islets among the acinar tissue, rather than isolated from it, which contributes to the interaction between exo-and endocrine cells of the pancreas [4].…”
Section: Introductionmentioning
confidence: 99%
“…Підвищений рівень TNF-a призводить до високого рівня системних реакцій, пов'язаних із запаленням та активацією зірчастих клітин, що, поряд зі значним підвищенням рівня TGF-b, вказує на прогресування дегенеративних процесів в уражених суглобах, а також на активне формування фіброзу ПЗ. Порушення імунного статусу у пацієнтів з ПОА на тлі зовнішньосекреторної недостатності ПЗ є спільною патогенетичною ланкою цих коморбідних явищ, що потребує поглибленого вивчення і розробки методів корекції [1][2][3].…”
unclassified